Updated Perspectives on The Diagnosis, Management And Novel Drug Delivery Strategies For The Treatment Of Onychomycosis (Journal of Pharmaceutical Negative Results, 2022)
Onychomycosis is a common fungal infection of the nail unit worldwide which poses a therapeutic challenge for both practitioners & patients and can cause pain, difficulty with ambulation and psycho-social problems. The infection is frequently due to dermatophyte, while yeast and non-dermatophyte molds (NDMs) attributed especially in immunocompromised patients. NDMs and Candida species can be involved as primary or secondary pathogens. Candida onychomycosis (CO), most commonly caused by C. albicans and C. parapsilosis, is frequently associated with local or systemic immune disturbances. In the cases that the host immunity is severely affected, Candida acts as primary pathogen, while other diseases e.g., diabetes mellitus, malnutrition, and smoking serve as predisposing factors for candida to cause secondary infection. Approximately 90% of toenail and 75% of fingernail onychomycosis are caused by dermatophytes, notably Trichophyton mentagrophytes and Trichophyton rubrum. Clinical manifestations include discoloration of the nail, subungual hyperkeratosis, onycholysis, candida granuloma, paronychia and onychauxis. Microscopy and fungal culture are the gold standard techniques for onychomycosis diagnosis, but high false-negative rates have pushed for more accurate methods, such as histology and PCR. As NDMs are skin and laboratory contaminants, their presence as an infectious agent requires multiple confirmations and repeated sampling. The conventional treatment of onychomycosis involves oral and topical therapy. Oral terbinafine, itraconazole and griseofulvin and topical ciclopirox 8% nail lacquer, efinaconazole 10% solution and tavaborole 5% solution, amorolfine 5% nail lacquer are approved by the Food and Drug Administration for treatment of onychomycosis. The oral antifungal agents though quite effective, are hepatotoxic and cause drug-drug interactions. Topical therapy is more patient compliant being devoid of such adverse effects but it suffers from another setback of improper nail penetration. Since decades, efforts have been made to enhance topical delivery for efficiently treating onychomycosis. Mechanical, physical and chemical methods have been employed. Despite all the attempts made, the nail delivery issues are far from being solved. Recently, the focus has shifted to novel drug delivery systems like nanoparticles, microemulsions, polymeric films and nail lacquers for enhanced drug permeation and localized therapy. The research around the world is exploring their potential as effective treatment options. The study aimed to provide an update on the evaluation, diagnosis, and treatment and further explore the novel delivery strategies to treat a persistent fungal infection like onychomycosis. Recent patents related to the management of onychomycosis are also discussed.